Effect of Particle Size and Fiber Loading on Some Properties of Sugarcane Bagasse Reinforced Unsaturated Polyester Composites - Shamsuddeen, Ruslan; Musa, Haruna; Mathew, Twan Sale; Abubakar, Musa Yahaya; Adam, Ansar Bilyaminu (Darul Yasin Al Sys, 2024)
In recent times, the use of sugarcane bagasse as reinforcement in plastic composites has been receiving greater scientific attention due to its abundance, light weight and good mechanical properties. This research has investigated the mechanical properties of the composite by hardness strength, impact strength, chemical resistant test, and water absorption test with different particle size and loading of sugarcane bagasse (SCB) as reinforcement in unsaturated polyester resin (UPR) composite. Bagasse fiber was treated with sodium hydroxide (10%), potassium permanganate (5%), hydrogen peroxide (5%) to enhance better adhesion between the fiber and the matrix. Sugarcane bagasse reinforced unsaturated polyester resin composite was prepared using the compression molding technique, the mold was undergoing a curing process for 5 minutes with 1300 c and 2.5Mpa of pressure. The result of the mechanical properties were eval_uated, the mechanical properties (flexural strength, hardness strength) increases with increase in bagasse content while the impact strength increase and then decreases, the maximum mechanical properties was obtained from the composite made of 400µ and 25 wt% fiber loading compared with the control sample. The improvement in the mechanical properties is attributed to the extent of good interaction between the fiber and the matrix. The composite show increase in water absorption with increasing fiber loading and increasing number of days up to when the samples reaches their saturation when no water absorption was observed, 25wt% of 710µ has the highest absorption and this is due to its bigger particle size and fiber loading. The mechanical and physical properties shows that the composite has potential applications in structural materials such as particle board, fiber board, library shelf’s, partitioning panels, ceiling boards.